Freedom and creativity as a way to knowledge of existential meanings (based on the Konstantin Moskalets’ essay "Month of admiring the moon") (Literatures of the World: Poetics, Mentality and Spirituality, 2019)
The article examines the problem of man’s searching for the meaning of being, which is interpreted inthe Konstantin Moskalets’ essay "Month of admiring the moon".There are thinkings about the artificiality and timeliness of the realities of "the present long time" and the loss of the word (language) of ability to reflect the true nature of things, phenomena, events,  states. According to the author, the spiritual man’s principle is primary and necessary. Without it man is only an amorphous mass which is wholy reigned by a body. Essay is intertextually linked to the Japanese cultural tradition (the title of the work, quotes from the Matsuo Basso’s haiku, allusions to the Japanese tea rite).The author interprets freedom and creativity as the necessary factors in the life of the individual, the noesis of his own essence, the liberation from the illusions of the modern world and  the path to God. There are thoughts  of need of  "the growth of being", the searching for authenticity, the aspiration to restore the true meaning of life and Word and spiritual insight.
Keywords: human; freedom; creativity; spirituality